Biological models in multiple sclerosis - Sanabria‐Castro, Alfredo; Flores‐Díaz, Marietta; Alape‐Girón, Alberto (Journal of neuroscience research, 2020)
Considering the etiology of multiple sclerosis (MS) is still unknown, experimental models resembling specific aspects of this immune‐mediated demyelinating human disease have been developed to increase the understanding of processes related to pathogenesis, disease evolution, evaluation of therapeutic interventions, and demyelination and remyelination mechanisms. Based on the nature of the investigation, biological models may include in vitro, in vivo, and ex vivo assessments. Even though these approaches have disclosed valuable information, every disease animal model has limitations and can only replicate specific features of MS. In vitro and ex vivo models generally do not reflect what occurs in the organism, and in vivo animal models are more likely used; nevertheless, they are able to reproduce only certain stages of the disease. In vivo MS disease animal models in mammals include: experimental autoimmune encephalomyelitis, viral encephalomyelitis, and induced demyelination. This review examines and describes the most common biological disease animal models for the study of MS, their specific characteristics and limitations.